Judith Scott: Capturing the Texture of Sensation. (3rd July 2021) - Mitchell, Victoria
Abstract: This paper considers a photograph by Leon A. Borensztein of the artist Judith Scott, taken in the Creative Growth Arts Center in California in 1997. It explores notions of affect and the mobilization of feeling on the part of the artist and artwork, photographer and viewer, with consideration of the way in which textile associations are central to the affective passage of transmission and encounter. A textile-skin interface between the haptic and the scopic is seen to characterize both the performative arena of the subject matter and the intricacy of the photograph's surface. Scott's textile-rich practices as an artist and her biographical circumstances are considered as intrinsic to the affective potency of the image. Didier Anzieu's notion of the skin envelope further enriches analysis of the bond that is established within the performative arena of the image and the sensations that are embodied in the viewer's response.